Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/ajt.13829
|View full text |Cite
|
Sign up to set email alerts
|

Should Asymptomatic Bacteriuria Be Systematically Treated in Kidney Transplant Recipients? Results From a Randomized Controlled Trial

Abstract: The indication for antimicrobial treatment of asymptomatic bacteriuria (AB) after kidney transplantation (KT) remains controversial. Between January 2011 and December 2013, 112 KT recipients that developed one episode or more of AB beyond the second month after transplantation were included in this open-label trial. Participants were randomized (1:1 ratio) to the treatment group (systematic antimicrobial therapy for all episodes of AB occurring ≤24 mo after transplantation [53 patients]) or control group (no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
1
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 31 publications
8
119
1
10
Order By: Relevance
“…Systematic screening and treatment of AB beyond the second month after transplantation provided no apparent benefit among KT recipients when the occurrence of acute pyelonephritis at 24-month follow-up was considered. The treatment also did not affect the secondary outcomes, which included lower UTI, acute rejection, Clostridium difficile infection, colonization or infection by multidrug-resistant bacteria, graft function and all-cause mortality [29].…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 98%
“…Systematic screening and treatment of AB beyond the second month after transplantation provided no apparent benefit among KT recipients when the occurrence of acute pyelonephritis at 24-month follow-up was considered. The treatment also did not affect the secondary outcomes, which included lower UTI, acute rejection, Clostridium difficile infection, colonization or infection by multidrug-resistant bacteria, graft function and all-cause mortality [29].…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 98%
“…We thank Orig€ uen et al for reporting the results of the first randomized controlled trial comparing antibiotics versus no treatment in kidney transplant recipients with asymptomatic bacteriuria (1). In view of the dramatic rise of multidrug-resistant bacteria in solid organ transplantation and because bacteriuria is considered to be the first reason for administrating antibiotics after kidney transplantation, we strongly believe that this research question is of importance.…”
Section: Old Habits Die Hard: Screening For and Treating Asymptomaticmentioning
confidence: 99%
“…Giral, et al [22] observed that APN occurring within the first 3 months of the transplant was associated to graft loss. Nevertheless, Abott, et al [23] in a retrospective cohort study of 28.942 renal transplant recipients in the USA observed that UTI occurring 6 months after the trans- the urinary tract, but only a clinical trial has addressed this matter, showing that although in the untreated group, 14% of patients the AB persisted for 7 months, and none developed symptomatic UTI [8].…”
Section: Impact Of Urinary Tract Infection On Graft Survivalmentioning
confidence: 99%
“…Urinary tract infections explain the main use of antibiotics in these patients [6]. It has been described that 25%-47% of renal recipients have at least one symptomatic UTI [7,8].…”
Section: Introduction Incidence and Burden Of Urinary Tract Infectionmentioning
confidence: 99%
See 1 more Smart Citation